A Review on the Evolution of Planned Health Education on the Knowledge and Practices of the Pregnant Mothers Attending Antenatal - Kashyap, Sweta; Singh, Charanjeet (Journal of Drug Delivery and Therapeutics, 2019)
The maternal health status of Indian women was noted to be lower as compared to other developed countries. Promotion of maternal and child health has been one of the most important components of the Family Welfare Programme of the Government of India. For sustainable growth and development of country, there is a need to improve MCH Care in the country. Antenatal care service is an important goal concerning in the health status of the pregnant women during their reproductive period and its health beneficial accounting for nearly one quarter of all pregnant worldwide. Early booking has an advantage for proper pregnancy information sharing and pregnancy monitoring. Unfortunately, adverse pregnancy outcome can occur even in women without identifiable risk factors Keywords: Antenatal Care, ANC, pregnancy, FANC.